Evaluation of the relationship between tooth decay and trabecular bone structure in pediatric patients using fractal analysis: a retrospective study - Dilara Nil Günaçar; Şengül Merve Erbek; Sema Aydınoğlu; Taha Emre Köse (European Oral Research)
Purpose: The movement of chewing affects the growth and development of the stomatognathic system. Tooth decay, which is known to have effects on chewing, can affect the jaw bone due to its indirect effect on the mechanical forces transmitted to the jaw bone. This study aimed to evaluate the relationship between dental caries and jawbone trabeculation during the growth and development processes in children using fractal dimension (FD) analysis. Patients and methods: A total of 120 patients were divided into three groups. The groups were determined as follows: group 1: 40 patients without deep dentin caries/apical rarefying osteitis, group 2: 40 patients with deep dentin caries/apical rarefying osteitis on the right or left sides, and group 3: 40 patients with deep dentin caries/apical rarefying osteitis on either the right and left side. Digital panoramic images of the selected patients were evaluated using FD analysis. Results: There was no statistically significant difference in the FD analysis among the groups (p>0.05). Age and sex factors were not found statistically significant in the in-group evaluation (p>0.05). In group 3, FD values of the right condyle (r= -0.42, p<0.05), right ramus (r= -0.37, p<0.05) and left ramus (r= -0.45, p<0.05) were negatively correlated with age. Conclusion: There is no relationship between tooth decay and trabeculation of the jawbone in children aged 8-13 years.